Warming and water deficit impact the nutritional performance of a C4 and C3 tropical grass - Viciedo, Dilier Olivera [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Global warming is predicted to increase the intensity and duration of extreme weather events, such as droughts, heat waves, and floods, especially in tropical regions. Climate change affect growth of forage species. However, information regarding the effects of global climate change on the nutritional performance of tropical pastures is lacking, especially under field conditions. We, thus, conducted two field experiment with Panicum maximum and Stylosanthes capitata using a temperature free-air controlled enhancement system and evaluated the effects of two temperature conditions, ambient temperature and moderate warming (2°C above ambient canopy temperature), and two levels of water availability, irrigated and non-irrigated, on nutrients accumulation, nutrient use efficiency (NUE), the stoichiometric patterns of C:N:P and leaf biomass production. Both experiments was conducted using a randomized complete block design in a factorial arrangement. Our findings revealed in plants of P. maximum (C4- grass) that the N and P leaf concentration greatly decreased under water-stressed, which increased the C:N and C:P ratios, while warming increased the N:P ratio. Leaf biomass production was impaired by up to 16% under water stress and ambient temperature conditions, but the biomass production was improved by 20% under warming and irrigated conditions. Our results also showed that homeostatic instability under rainfed conditions resulted in decreased leaf biomass production, and it was concluded that warming is only beneficial for plant growth under well-irrigated conditions. Meanwhile, drought decreased NUE of K, Ca, and B and the leaves dry biomass, while root growth was stimulated. However, under combined warming and irrigation increased the leaves dry biomass, root dry biomass, root length density, root surface area and the NUE of N, P, K, Ca, Mg, Cu, Mn, and Zn. On the other hand, in the second experiment with plants of S. capitata (C3-pasture), our results showed that drought conditions decreased phosphorous (P) concentrations and increased N:P ratio in different plant organs. We found that aboveground biomass production declined significantly under drought and high temperature conditions (wSaT and wSeT); we observed a decrease in nitrogen (N) content, a decrease in leaf/inflorescence and leaf/stem ratios, and an increase in C:N ratio in vegetative organs. However, under warm and well-irrigated conditions, the leaf biomass increased approximately 33%. We have concluded that warm and well-watered conditions without restrictions in soil nutrient availability can enhance plant production, presumably due to a higher level of stoichiometric homeostasis.

Prevê-se que o aquecimento global aumente a intensidade e a duração dos eventos climáticos extremos, como secas, ondas de calor e inundações, especialmente nas regiões tropicais. Mudanças climáticas afetam o crescimento de espécies forrageiras. No entanto, faltam informações sobre os efeitos das mudanças climáticas globais no desempenho nutricional de pastagens tropicais, especialmente em condições de campo. Nós, assim, conduzimos dois experimento em campos com as forrageiras Panicum maximum e Stylosanthes capitata utilizando um sistema de temperatura controlada do aquecimento do ar (T-Face) e avaliou-se os efeitos de duas condições de temperatura, (temperatura ambiente) e aquecimento moderado (2°C acima da temperatura ambiente) e dois níveis de disponibilidade hídrica, (irrigada e não irrigados), no acúmulo de nutrientes, eficiência de uso de nutrientes (NUE), nos padrões estequiométricos de C:N:P e na produção de biomassa foliar. Ambos experimentos foram conduzidos utilizando um delineamento de blocos completos casualizados em arranjo fatorial. Nossos resultados revelaram que em plantas de P. maximum (pastagem C4) a concentração foliar de N e P diminuiu sob estresse hídrico, o que aumentou as relações C:N e C:P, enquanto o aquecimento aumentou a relação N:P. A produção de biomassa foliar foi prejudicada em até 16% sob condições de estresse hídrico e temperatura ambiente, mas a produção de biomassa foi melhorada em 20% sob condições de aquecimento e irrigação. Nossos resultados também mostraram que a instabilidade homeostática em condições de seca resultou na diminuição da produção de biomassa foliar, e concluiu-se que o aquecimento é benéfico apenas para o crescimento das plantas em condições bem irrigadas. Enquanto isso, a seca diminuiu a NUE de K, Ca e B e a biomassa seca das folhas, enquanto o crescimento das raízes foi estimulado. No entanto, sob aquecimento e irrigação aumentaram a biomassa seca das folhas, a biomassa seca das raízes, a densidade do comprimento das raízes, a área superficial da raiz e a NUE de N, P, K, Ca, Mg, Cu, Mn e Zn. Por outro lado, no segundo experimento com plantas de S. capitata (pastagem C3), nossos resultados mostraram que as condições de seca reduziram as concentrações de fósforo (P) e aumentaram a relação N:P nos diferentes órgãos da planta. Descobrimos que a produção de biomassa acima do solo diminuiu significativamente sob condições de seca e de alta temperatura (wSaT e wSeT); observamos uma diminuição no conteúdo de nitrogênio (N), na relação folha/inflorescência e relação folha/caule, e um aumento na relação C:N nos órgãos vegetativos. No entanto, sob condições quentes e irrigação, a biomassa das folhas aumentou aproximadamente 33%. Concluímos que o aquecimento em condições bem regada e sem restrições na disponibilidade de nutrientes no solo, pode aumentar a produção de biomassa vegetal, presumivelmente devido a um nível mais alto da homeostase estequiométrica.
O aquecimento e déficit hídrico impactam o desempenho nutricional de uma forrageira tropical C4 e C3
Keywords: Tropical pasture; Nutrients uptake; Combined stresses; Climate change; Stoichiometric homeostasis